GENDER INFLUENCE FOR GRAMMAR UNDERSTANDING IN ENGLISH STUDENTS 2018-A OF STKIP PGRI JOMBANG - Dhea Adelina (LPPM STKIP PGRI Sidoarjo, 2019)
Grammar is the science that teaches how to compose words to become a sentence correctly. According to Gleason and Ratner, 2009: 231-269;Thornbury, 1999 that grammar is a set of rules that explores the forms and structures of sentences that can be used in a language. Some people assume that gender is very influential in understanding something. Female are considered more perceptive in understanding a thing while the male are more sluggish in understanding a thing. According to Grey (2001) convey that female have the verbal intelligence (language) than male. The type of the research was analytic observational with Microsoft Excel. The study was conducted in English students 2018-A of STKIP PGRI JOMBANG. The population in this study was English students 2018-A o f STKIP PGRI JOMBANG. The sample in this study was 10 students that consist 5 male students and 5 female students. The research instrument to collect data was a questioners. The results showed that Gender influences the results of students' understanding of grammar. The factor that most influences the results is the level of student learning. Female is more diligent than male, evidenced by female learning English. Therefore the researchers want to find out a difference in student learning outcomes and there are factors that cause a difference in student learning results for male and female students 2018A English Students of STKIP PGRI JOMBANG.